TECHNOLOGY INTEGRATION IN LANGUAGE TEACHING (Web of Teachers: Inderscience Research, 2024)
The article analyzes the impact of technology on the process of teaching foreign languages, examines the advantages and challenges of their integration into the educational process. Technologies such as digital platforms, learning applications, virtual reality, artificial intelligence, as well as various methods of using technology to develop language skills are discussed. The article provides examples of successful practices, as well as recommendations for the effective implementation of technology in teaching. The main focus is on how technology helps motivate students and improve the quality of the educational process.